2008
DOI: 10.1159/000142044
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin C1 from Apple Extracts Inhibits FcεRI-Mediated Mast Cell Activation

Abstract: Background: Polyphenol-enriched fractions, which are extracted from unripe apples (Rosaceae, Malus spp.), consisting of procyanidins (polymers of catechins) are known to have an anti-allergenic effect on patients with various allergic diseases. Although it has been reported that apple extracts inhibit histamine release from mast cells, the molecular mechanisms for this anti-allergenic effect are not well understood. To elucidate the molecular mechanisms by which apple extracts induce their anti-allergenic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 57 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…In vitro studies have demonstrated the inhibitory effects of flavonoids on FcRI surface molecule or gene expression [40,41]. Although mast cells were not determined histologically in the intestine, from…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In vitro studies have demonstrated the inhibitory effects of flavonoids on FcRI surface molecule or gene expression [40,41]. Although mast cells were not determined histologically in the intestine, from…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There are many reports on the biological activities of cinnamic acid or cinnamaldehyde, for example, induction of ROS-mediated apoptosis (19). In addition, the procyanidin C1 we purified is known for its anti-inflammatory effects (20,21); however, it is the first time to show that procyanidin C1 has anti-metastatic or anti-EMT effects. Among the catechin sub-family, epigallocatechin-3 gallate in green tea has been reported to inhibit EMT in human melanoma cells (22,23).…”
Section: Discussionmentioning
confidence: 97%
“…PG102, an aqueous extract from Actinidia arguta (26), is an example exhibiting such an activity. White rose fetal extract of Rosa rugosa root (27), procyanidin C1 from apple (28), and hot water extract of Cydonia oblonga (29) have shown potential in inhibiting chemical-induced animal model or NC/Nga mice. In the course of screening of anti-atopic agents, we found that an aqueous TcRSE exhibits in vitro antioxidant and free radical-scavenging capability, and has potent T-bet promoter enhancing activity.…”
Section: Discussionmentioning
confidence: 99%